Application of asymmetric Si3N4 hollow fiber membrane for cross-flow microfiltration of oily waste water. Issue 13 (October 2018) - Abadikhah, Hamidreza; Zou, Cai-Neng; Hao, You-Zhi; Wang, Jun-Wei; Lin, Li; Khan, Sayed Ali; Xu, Xin; Chen, Chu-Sheng; Agathopoulos, Simeon
Graphical abstract: Highlights: Cross sectional adjustment of Si3 N4 hollow fiber membrane for microfiltration of oil/water emulsion. Thorough study of the effect of the operating parameters on permeate flux and oil rejection. Comprehensive study of the fouling (including modeling) of the membranes. Complete (≥99%) recovery of fouled membranes after high treatment at 400 °C. Abstract: The asymmetric morphology of silicon nitride (Si3 N4 ) ceramic hollow fiber membrane with a selective spongiform outer layer was optimized by the air gap distance and the internal rate of coagulate for oil/water emulsion microfiltration. The effect of trans-membrane pressure (TMP), feed flow rate (FFR), and pH of the feeding emulsion on the separation performance were determined experimentally. Membrane fouling has increased by dissociation of oil droplets during filtration at high TMP and FFR values. Fouling phenomena were studied based on standard pore blocking model. The pH by affecting the surface charge of the Si3 N4 hollow fibers and zeta potential of the feed emulsion has also been introduced as a prominent influential factor on separation efficiency. The highest values of permeate flux (390 Lm −2 h -1 ) and oil rejection (95%) were recorded in alkaline pH. The fabricated Si3 N4 ceramic membranes were completely recovered (≤99%) by simple thermal treatment at 400 °C.